2004
DOI: 10.1111/j.1432-1033.2004.04164.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection of chylomicron remnants from oxidation by incorporation of probucol into the particles enhances their uptake by human macrophages and increases lipid accumulation in the cells

Abstract: The effects of protection of chylomicron remnants from oxidation on their uptake and induction of lipid accumulation in macrophages were investigated using chylomicron remnant-like particles (CRLPs) containing the lipophilic antioxidant drug, probucol, and macrophages derived from the human monocyte cell line, THP-1. The total lipid content of THP-1 macrophages was markedly higher (·2.2) after 48 h of incubation of THP-1 macrophages with CRLPs containing probucol (pCRLPs) when compared to CRLPs without probuco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 65 publications
(106 reference statements)
4
24
0
Order By: Relevance
“…However, as it is difficult to obtain chylomicron remnants from human blood uncontaminated with lipoproteins of similar density, such as chylomicrons and VLDL, it was necessary to use model CRLP to mimic the action of the remnant lipoproteins. Radiolabelled compounds can easily be incorporated into the model particles, and CRLP provide a suitable and convenient model for our studies on chylomicron remnant metabolism in macrophages [9, 19, 27]. The size, density and lipid composition of the CRLP used was similar to that of physiological remnants [8, 17, 28], and they also contained human apoE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as it is difficult to obtain chylomicron remnants from human blood uncontaminated with lipoproteins of similar density, such as chylomicrons and VLDL, it was necessary to use model CRLP to mimic the action of the remnant lipoproteins. Radiolabelled compounds can easily be incorporated into the model particles, and CRLP provide a suitable and convenient model for our studies on chylomicron remnant metabolism in macrophages [9, 19, 27]. The size, density and lipid composition of the CRLP used was similar to that of physiological remnants [8, 17, 28], and they also contained human apoE.…”
Section: Discussionmentioning
confidence: 99%
“…However, the CRLP used in the present study were not oxidized and, in addition, to date, there is little evidence for a leading role of scavenger receptor-mediated uptake of chylomicron remnants [8, 9, 11, 24]. Furthermore, the protection of chylomicron remnants from oxidation enhances, rather than inhibits, their induction of lipid accumulation in macrophages [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mRNA for the ABCA-1 (ATPbinding cassette transporter A-1), which is involved in the efflux of cholesterol from macrophages, was decreased by CRLPs, but raised by oxCRLPs [23]. In addition, we have found that the incorporation of lipophilic antioxidants such as the tomato pigment, lycopene, or the drug, probucol, into CRLPs markedly increases lipid accumulation in THP-1 macrophages, and that this is due to more rapid uptake of the particles [26,27]. Further investigations in our laboratory using CRLPs, oxCRLPs (oxidized by exposure to CuSO 4 ) and CRLPs containing probucol (pCRLPs) have shown that the rate of uptake of the particles by THP-1 macrophages and the amount of lipid subsequently accumulated is inversely related to the oxidative state of the particles.…”
Section: The Effect Of Oxidation Of Cmrs On Their Uptake and Inductiomentioning
confidence: 77%
“…Since it is difficult to separate chylomicron remnants from other lipoproteins of similar density in human blood such as chylomicrons and VLDL, model CRLPs containing human apoE were used in our experiments. Such particles have been used extensively in previous studies both in our laboratory (Goulter et al, 2002;Moore et al, 2003Moore et al, , 2004Batt et al, 2004;Botham et al, 2005) and others' (Diard et al, 1994;Redgrave et al, 1982Redgrave et al, , 1993 and have been found to be similar to physiological remnants in their size, density and lipid composition, and to mimic the effects of physiological remnants in rat hepatocytes and pig endothelial cells as well as in human macrophages.…”
Section: Discussionmentioning
confidence: 95%